Characterization of Building Thermal Energy Consumption at the Urban Scale. (November 2016) - Mutani, Guglielmina; Delmastro, Chiara; Gargiulo, Maurizio; Corgnati, Stefano P.
Abstract: The ongoing urban transition toward decarbonized energy systems has raised the attention on local energy planning practices. Besides the multiple actors involved in the planning process, the complexity of the urban energy systems requires the elaboration of heterogeneous data. In such contest, the paper introduces and compares two GIS-based methodologies for supporting the spatial characterization of the local residential built environment in terms of building distribution and space heating energy consumption. Starting from the assessment of residential consumption, a third method for the characterization of non-residential building thermal energy consumption is proposed. From a bottom-up perspective, in both residential models all the buildings are geo-referenced and clustered according to their thermo-physical characteristics. From a top-down perspective, energy balance data are used to calibrate the bottom-up results and to match the total building loads. The procedure, tested on the city of Turin as case study, allows assessing the energy use of buildings and to create urban energy maps. The energy spatial characterization of a territory is the basis for performing short and long-term scenarios analysis. Results of this method can be useful to: i. decision maker to understand the current state of the territorial energy consumption to identify critical energy intense areas; ii. citizens for visualising their energy consumption and iii. researchers for setting up the basis of further urban analysis.